Chapter 5: Experimental and computational approaches to study membranes and lipid-protein interactions - Sengupta, Durba; Kumar, G. Aditya; Prasanna, Xavier; Chattopadhyay, A. (Computational biophysics of membrane proteins, 2017)
Biological membranes are complex two-dimensional, non-covalent assemblies of a diverse variety of lipids and proteins. A hallmark of membrane organization is varying degrees of spatiotemporal heterogeneity spanning a wide range. Membrane proteins are implicated in a wide variety of cellular functions, and comprise ∼30% of the human proteome and ∼50% of the current drug targets. Their interactions with membrane lipids are recognized as crucial elements in their function. In this article, we provide an overview of experimental and theoretical approaches to analyze membrane organization, dynamics, and lipid-protein interactions. In this context, we highlight the wide range of time scales that membrane events span, and approaches that are suitable for a given time scale. We discuss representative fluorescence-based approaches (FRET and FRAP) that help to address questions on lipid-protein and protein-cytoskeleton interactions in membranes. In a complimentary fashion, we discuss computational methods, atomistic and coarse-grain, that are required to address a given membrane problem at an appropriate scale. We believe that the synthesis of knowledge gained from experimental and computational approaches will enable us to probe membrane organization, dynamics, and interactions at increasing spatiotemporal resolution, thereby providing a robust model for the membrane in health and disease.